Balancing Act: An Approach for Organization Management in the 21st Century - Thapa, Ajay (Journal of Development and Social Engineering, 2017)
The main purpose of this paper is to discuss why the balancing act is an important approach in leading or managing public and private organizations in the 21st century. The paper presents a brief concept of the terms; exhibits a critical discussion on the application of balancing act between the various approaches of organization management such as continuity and diversity, individual and organization incentive, conformity and individualism, centralization and decentralization, face to face and distant communications, and different but complementary roles into public and private organizations; and finally draws a conclusion. The paper is expected to be useful for the leaders and/or managers of public and private organizations to manage organizations efficiently and effectively.